Drivers of Agricultural Funding in a Post Partially Dollarized Zimbabwe - Mbira, Leonard; Moyo, Sherman (Journal of Economics and Behavioral Studies, 2018)
Agriculture has long been the backbone of the Zimbabwean economy contributing in excess of 40% at its peak. There has been a sharp decline in the performance of this sector over the years especially from 2000. Concurrently the sector has been struggling to access financing from the conventional financial system despite its strategic importance to the economy. This study sought to unravel the major fundamentals behind the financing vacuum in the agricultural sector. It adopts a survey approach for data collection and applies both descriptive and inferential methods . A questionnaire was used for data collection on a sample of 117 respondents comprising of farmers’ representatives, bank employees and ministry of agriculture officials. Data was analyzed using SPSS’ Analysis of Moment Structures software which allows for structural equation modeling to identify multiple relationships among variables simultaneously. The study identifies the efficient and reliable value chain mechanism, volatile government policy, short term deposits experienced by banks, land tenure system and lack of investor confidence as the underlying fundamentals behind the low financing in agriculture.